Maternal Prepregnancy BMI and Glucose Level at 24–28 Gestational Weeks on Offspring's Overweight Status within 3 Years of Age. (30th January 2017) - Li, Weiqin; Wang, Leishen; Li, Nan; Li, Wei; Liu, Huikun; Zhang, Shuang; Hu, Gang; Leng, Junhong
Abstract : Objective . To examine the relative impact of maternal prepregnancy body mass index (BMI) and glucose level at 24–28 gestational weeks on offspring's overweight status from birth to 3 years of age in China. Methods . Health care records of 21, 354 mother-child pairs were collected. The single and joint associations of maternal prepregnancy BMI and glucose level at 24–28 gestational weeks with 0–3-year-old offspring's overweight status were assessed. Results . The odds ratios (95% confidence intervals) of offspring's macrosomia at birth and overweight/obesity at the 12th month, 24th month, and 36th month were 1.12 (1.11–1.13), 1.05 (1.04–1.06), 1.07 (1.06–1.08), and 1.11 (1.10–1.12) for each 1-unit increase (km/m 2 ) in maternal prepregnancy BMI and 1.13 (1.10–1.17), 1.01 (0.99–1.03), 0.99 (0.96–1.01), and 1.00 (0.97–1.02) for each 1-unit increase (mmol/L) in maternal glucose level at 24–28 gestational weeks, respectively. The positive association of maternal glucose level with macrosomia at birth was similar between prepregnancy normal weight (BMI < 24 kg/m 2 ) and overweight (BMI ≥ 24 kg/m 2 ); however, the positive association of high maternal glucose level with childhood overweight was only seen among prepregnancy normal weight mothers but not among overweight mothers. Conclusions . The impact of maternal gestational hyperglycemia on offspring's overweight before 3 years of age can be modified by prepregnancy BMI.